Medical biotechnology - Glick, Bernard R. (ASM Press, 2014)
This concise introductory text provides a complete overview of biodiversity - what it is, how it arose, its distribution, why it is important, human impact upon it, and what should be done to maintain it. Timely overview of the serious attempts made to quantify and describe biodiversity in a scientific way Acts as an easy entry point into the primary literature Provides real-world examples of key issues, including illustrations of major temporal and spatial patterns in biodiversity Designed primarily with undergraduate students and course lecturers in mind, it will also be of interest to anyone who requires an overview of, and entry to, the vast literature on these topics. All the figures included in the book are downloadable from the Blackwell Publishing website